Implementasi Manajemen Strategi Bank Syariah Indonesia (BSI) Tbk, Cabang Banda Aceh dalam Meningkatkan Kualitas Mutu Pelayanan Nasabah - Harahap, Wahyuni; Zuliani; Fajri, Ikhsan; Hamid, A.; Mauliza, Putri (Jurnal EMT KITA, 2025)
This research is titled "Implementation of Strategic Management of PT. Bank Syariah Indonesia (BSI) Tbk, Banda Aceh Branch in Improving the Quality of Customer Service. Along with the fierce competition in today's banking world, Islamic banking, especially Bank Syariah Indonesia, wants to provide the implementation of strategic management in improving the quality of service, especially in serving customer needs, with good service, customers and the public will feel satisfied and believe in what is important for the bank, the form of service provided includes receiving complaints or problems faced by a customer. Bank Syariah Indonesia must be good at finding solutions or strategic management in managing (solving) the problems faced by its customers. Based on the initial observations, this study was carried out by observation in general on PT. Bank Syariah Indonesia (BSI) Banda Aceh Branch. However, there are several obstacles that occur, including in terms of the lack of services carried out as seen from the existence of several operational networks of Bank Syariah Indonesia that have not been maximized, the level of independence, quality and quantity of some employees who are still problematic, which is marked by the failure of the data input system, transactions, which had occurred in the last year, this has an impact on the less effective service to customers by a small number of employees PT. Bank Syariah Indonesia (BSI) Banda Aceh Branch. Based on the phenomena that occur in the field, the objectives of this study are; "To find out the Strategic Management of Bank Syariah Indonesia (BSI) Tbk Peunayong Unit Banda Aceh Branch in improving the Quality of Customer Service by conducting a literature review through the literature of scientific papers, books and other literature that is relevant to the research.